Using perturbations in elite men`s squash to generate performance profiles. - Murray, S.; Howells, M.; Hurst, L.; Hughes, M. T.; Hughes, M.; James, N. (World Congress of Performance Analysis of Sport VIII, 2008)
It can be concluded that perturbations can be reliably identified in squash, meaning squash can be considered a dynamic system that transits from bouts of stability to instability. Evidence of multiple perturbations in a rally was also established. The three main shots that caused perturbations were the boast, drop and volley drop indicating going short causes most disturbances in the system. The backhand side at the back of the court was where most perturbations were played. After comparing the perturbation profile to the winner and error profiles significant differences were found between the two profiles, indicating perturbations provide further in-depth analysis of notational analysis of squash. After conducting a case study on two elite male players it was found that there were significant differences between the two players` profiles. Subject 1 used perturbations in a more attacking style whereas Subject 2 used perturbations in a defensive way showing variations in the use of perturbations.